Best multi Approximation of Unbounded Functions by Using Modulus of Smoothness - Omar Khashan; Alaa Auad; Ghassan Ezzulddin Arif (مجلة جامعة الانبار للعلوم الصرفة, 2021)
We present an estimate of the degree of best multi approximation of unbounded function on 〖[-1,1]〗^d by algebraic polynomials in weighted space. The studied of the relation between the best approximation of derivatives functions in weighted space and the best approximation of unbounded functions in the same space.